Narrativas no ensino de artes visuais em Juazeiro-BA e Petrolina-PE - Vasconcelos, Flávia Maria de Brito Pedrosa (2011)
This research seeks to understand how the teaching of Visual Arts is conceived in the cities of Juazeiro (Bahia state) and Petrolina (Pernambuco state). To do this, I use the narratives presented in discourses of four teachers who work with Visual Arts in the Art discipline in two public schools, one of each city, with significant IDEB (the Brazilian education quality index) in 2005, 2007 and 2009. The research focus is on concepts, observed in teaching approaches and didatical procedures, which can be found in the pedagogical practice of the universe studied. I search to investigate how the four teachers who participated of the research conceive their education practices in Visual Arts teaching at school (6th to 9th grade). This study begins with the notion that theories involving educational practice can be constructed as an aid for understanding the initial and continuing teacher education for a better quality of Visual Arts teaching. I elicit the methodological ways that the educational narratives provide as a qualitative research. In this sense, I contextualize it making a brief geographical description and a situational look through which the research relates with the use of some visualities that the teachers infer as present in their education practice. I expose the conceptions of two Art teaching approaches common in the Brazilian context, the Triangular Approach and the Education in Visual Culture . I reflect on how these approaches are stated or implied in discourses, making use of a questionnaire and of a semi-structured interview, both answered individually by the four teachers. I also reflect upon the Visual Arts teachers´s narratives as starting points for thinking about the initial and continuing education for Art teachers, among other issues flagged in the universe studied.